On the Effectiveness of Elected Male and Female Leaders and Team Coordination - Ernesto Reuben; Krisztina Timko (Institute of Labor Economics (IZA), 2017)
We study the effect on coordination in a minimum-effort game of a leader's gender depending on whether the leader is democratically elected or is randomly-selected. Leaders use non-binding messages to try to convince followers to coordinate on the Pareto-efficient equilibrium. We find that teams with elected leaders coordinate on higher effort levels. Initially, the benefits of being elected are enjoyed solely by male leaders. However, this gender difference disappears with repeated interaction as unsuccessful male leaders are reelected more often than unsuccessful female leaders.
Keywords: M14; M54; J16; C92; 330; gender differences; leadership; democracy effect; leader effectiveness; coordination